Post-fire mortality in mixed forests of central Portugal - Catry, Filipe (2015)
Wildfires are a recurrent disturbance in the Mediterranean Basin. However, managers from this region are confronted with a lack of information on the effects of fire on most woody species, which is required for defining sustainable forest management strategies. Following a large wildfire in central Portugal (2003), we surveyed the area during the first year and assessed the vegetative condition of 1040 burned trees from 11 different species. Among those trees, 755 individuals were selected and monitored annually for 4 years. At the end of the study, almost all the broadleaved trees survived, while most coniferous died. In spite of the low mortality observed in broadleaves, most were top-killed and regenerated only from basal resprouts, which implies a slow recovering process. Quercus suber, however, showed vigorous post-fire crown resprouting and was the most resilient species. We fitted logistic regression models to predict the probability of individual tree mortality and top-kill from fire injury indicators and tree characteristics. Besides the differences between the two main functional groups (coniferous, broadleaved), bole char height and crown volume scorched or consumed were important predictors of tree responses. Additionally, the main factor determining crown mortality on broadleaved species was bark thickness. The selected models performed well when tested with independent data obtained on four other wildfires. These models have several potential applications and can be useful to managers making pre-fire or post-fire decisions in mixed forest stands in the western Mediterranean Basin.